Advances and prospects of mucosal vaccination in the prevention and control of avian influenza - Hui, Xianfeng; Tian, Xiaowei; Ding, Shihuan; Gao, Ge; Gao, Shuoxiang; Sun, Aiping; Zhao, Tiesuo; Wang, Hui (Frontiers in Immunology, 2026)
Avian influenza virus (AIV) poses a persistent threat to global poultry production and public health. Long-term immunization programs have established a foundational immune barrier, significantly mitigating the risk of highly pathogenic avian influenza outbreaks. However, the high mutability of AIV, complex biosafety requirements, and the accelerating scale of poultry production underscore the need for enhanced mucosal protection. Mucosal immunity represents a critical defense against respiratory virus invasion in poultry, rapidly mobilizing local antibodies, cellular immune responses, and innate defense mechanisms. Recent advances in mucosal vaccine platforms—including viral vectors, nucleic acid vaccines, nanoparticle-based delivery systems, and water- or spray-administered formulations—have demonstrated potential in poultry models to enhance local immune responses, reduce viral shedding, and improve herd-level immune uniformity. This review provides a systematic overview of the unique structural and immunological features of avian mucosal tissues, summarizes the latest developments in mucosal vaccine technologies, and discusses their potential applications and challenges within integrated avian influenza control strategies.